2002
DOI: 10.1099/0022-1317-83-3-651
|View full text |Cite
|
Sign up to set email alerts
|

Dual-colour imaging of membrane protein targeting directed by poa semilatent virus movement protein TGBp3 in plant and mammalian cells

Abstract: The movement function of poa semilatent hordeivirus (PSLV) is mediated by the triple gene block (TGB) proteins, of which two, TGBp2 and TGBp3, are membrane proteins. TGBp3 is localized to peripheral bodies in the vicinity of the plasma membrane and is able to re-direct TGBp2 from the endoplasmic reticulum (ER) to the peripheral bodies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
56
0
5

Year Published

2005
2005
2018
2018

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(71 citation statements)
references
References 93 publications
(130 reference statements)
9
56
0
5
Order By: Relevance
“…The above findings are in general agreement that the movement proteins of several viruses may associate with the endomembrane system (see Oparka, 2004) and are in line with the reported localization of TGB proteins of Poa semilatent hordeivirus (PSLV; Solovyev et al, 2000) and PVX Mitra et al, 2003), which in transient expression assays showed an association with the ER network or ER-derived structures at the cell periphery (Solovyev et al, 2000;Zamyatnin et al, 2002). Mutations in the predicted transmembrane domains of PVX TGB proteins that disrupt membrane binding inhibited the association with ER and virus movement Mitra et al, 2003).…”
Section: Introductionsupporting
confidence: 76%
See 2 more Smart Citations
“…The above findings are in general agreement that the movement proteins of several viruses may associate with the endomembrane system (see Oparka, 2004) and are in line with the reported localization of TGB proteins of Poa semilatent hordeivirus (PSLV; Solovyev et al, 2000) and PVX Mitra et al, 2003), which in transient expression assays showed an association with the ER network or ER-derived structures at the cell periphery (Solovyev et al, 2000;Zamyatnin et al, 2002). Mutations in the predicted transmembrane domains of PVX TGB proteins that disrupt membrane binding inhibited the association with ER and virus movement Mitra et al, 2003).…”
Section: Introductionsupporting
confidence: 76%
“…Moreover, TGB proteins are expressed at low levels and are not readily detectable in virus-infected plants. Therefore, in several studies, the role and functions of TGB2 and TGB3 proteins have been investigated using microinjection or biolistic bombardment to introduce plasmids for transient expression of fluorescent fusion proteins (Solovyev et al, 2000;Zamyatnin et al, 2002Zamyatnin et al, , 2004Krishnamurthy et al, 2003;Mitra et al, 2003). In addition, expression of fusion proteins from viral vectors has provided (G) GFP-Ara7 labels vesicles throughout the cytoplasm of the cell, seen here near the cell periphery (arrow) (green channel).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is possible that TGBp2 can direct TGBp3 to the same ER vesicles during viral infection. Studies prove that TGBp2 and TGBp3 sometimes coexist (Zamyatnin et al 2002). So far there has not been provided any data which would show whether TGBp2-related vesicles contain TGBp1, vRNA, CP or virus-like particles.…”
Section: Tgb Cooperating Systemmentioning
confidence: 99%
“…En lo que respecta a las proteínas TGBp2 y TGBp3, son productos de menor tamaño y funcionan como proteínas integrales de membrana en ambas clases de virus [Tamai & Meshi, 2001;Cowan et al, 2002;Zamyatnin et al, 2002;Krishnamurthy et al, 2003;Gorshkova et al, 2003]. El producto TGBp2, cuyo tamaño oscila entre 11-14 kDa, posee dos secuencias hidrofóbicas internas que median su inserción en RE, dejando la región intermedia hidrofílica, muy conservada, dispuesta a modo de lazo hacia la cara luminal del orgánulo y los extremos N-t y C-t expuestos al citoplasma [Zamyatnin et al, 2006;Hsu et al, 2008;Lee et al, 2010].…”
Section: Bloque Triple De Genesunclassified